THE RELATIONSHIP BETWEEN ACHIEVEMENT MOTIVATION AND FAMILY SUPPORT WITH STUDENT INVOLVEMENT IN INTEGRATED ISLAMIC SMP ULIL ALBAB PEMATANG SIANTAR - Fadilah Hasriana; Abdul Munir; Amanah Surbakti (RADJA PUBLIKA, 2023)
Empirically, this study aims to see the correlation between achievement motivation and family support with student involvement. Student engagement is the frequency with which students have a will in routine activities and school programs both inside and outside the classroom with behavioral, emotional and cognitive indicators during their studies at school. The population of this study were 120 students and 120 students as the research sample, with the sampling technique using the total sampling technique. The data collection technique used a scale, namely the student engagement scale, the achievement motivation scale and the family support scale. Data analysis techniques and hypothesis testing use the structural equation model-partial least squares (SEM-PLS) method. The results showed that the proposed hypothesis was accepted, namely: (1) there was a correlation between achievement motivation and student engagement, with a t-count of 2.623 > 1.96 and a p-value of 0.009 <0.05, and a significant positive correlation. (2) there is a correlation between family support and student engagement, with a t-count of 2.645 > 1.96 and a p-value of 0.008 <0.05, and a significant positive correlation. (3) there is a correlation between family support and student engagement, with an R2 value of 0.202 (20.2%), however, the correlation between the two independent variables is weak. 008 <0.05, and a significant positive correlation.